Alternative splicing regulation by tumor suppressing subtransferable candidate 4: a pathway to tumor suppression - Zhao, Haiping; Wu, Nana; Wei, Gaigai; Zhang, Huiling; Ren, Tingrong; Yi, Jingjing; Zhang, Yuqi; Wang, Zixi; Wang, Yihan; Guo, Zhihan; Zhang, Duanwu (Frontiers in Immunology, 2024)
IntroductionRNA splicing is a crucial posttranscriptional process that governs gene expression, and defects in alternative splicing contribute to various diseases, including cancer. Tumor suppressing subtransferable candidate 4 (TSSC4) is a known tumor suppressor and has been identified as part of the U5 small nuclear ribonucleoprotein (snRNP), which is involved in tri-snRNP biogenesis. However, the precise role of TSSC4 in regulating alternative splicing and its impact on tumor growth remain unclear.MethodsTo explore the link between splicing modulation and tumor suppression driven by TSSC4, we conducted transcriptome sequencing (RNA-seq) on TSSC4-knockout and wild-type HeLa cells. Additionally, we analyzed alternative splicing and gene expression in various cancer cell lines, including TSSC4-knockout A549 cells and TSSC4-knockdown PANC-1, MDA-MB-231, and MCF-7 cells. Splicing patterns and gene expression profiles were compared between TSSC4-deficient and control cells.ResultsOur RNA-seq analysis revealed that TSSC4 deficiency in HeLa cells results in widespread alterations in splicing patterns and gene expression. Specifically, the loss of TSSC4 led to abnormal alternative splicing events and dysregulation of tumor-associated genes, including several oncogenes. This effect was confirmed across multiple cancer cell lines, highlighting a consistent role of TSSC4 in splicing regulation.DiscussionThese findings demonstrate that TSSC4 plays a crucial role in regulating RNA splicing, particularly in controlling the splicing of many oncogenes. Our results reveal a novel mechanism by which TSSC4 mediates tumor suppression through the modulation of alternative splicing, which could provide implications for understanding TSSC4’s role in cancer biology.